H7N9 Avian Influenza Virus Is Efficiently Transmissible and Induces an Antibody Response in Chickens - Jiao, Peirong; Song, Yafen; Huang, Jianni; Xiang, Chengwei; Cui, Jin; Wu, Siyu; Qu, Nannan; Wang, Nianchen; Ouyang, Guowen; Liao, Ming (Frontiers in Immunology, 2018)
H7N9 viruses pose a threat to human health and they are no less harmful to the poultry industry than the H5N1 avian influenza viruses. However, the pathogenesis, transmissibility, and the host immune response of the H7N9 virus in chickens and mice remain unclear. In this study, we found that H7N9 viruses replicated in multiple organs of the chicken and viral shedding persisted up to 30 days post-inoculation (DPI). The viruses were efficiently transmitted between chickens through direct contact. Notably, chickens infected with H7N9 had high antibody levels throughout the entire observation period and their antibody response lasted for 30 DPI. The expression levels of the pattern-recognition receptors (PRRs) and pro-inflammatory cytokines were found to be significantly up-regulated in the brain using quantitative real-time PCR. The expression of TLR3, TLR7, MDA5, Mx, IL-1β, IL-6, IFN-ɑ, and IFN-γ were also significantly different in the lungs of infected chickens. We found that the viruses isolated from these birds had low pathogenicity in mice, produced little weight loss and could only replicate in the lungs. Our findings suggested that the H7N9 viruses could replicate in chickens and mice and be efficiently transmitted between chickens, which presented a significant threat to human and poultry health.